Conservative outlook, gender norms and female wellbeing: Evidence from rural Bangladesh. (November 2018) - Ahmed, Tanima; Sen, Binayak
Highlights: We conceptualize the possible association between conservative outlook and female well-being. We define conservative outlook as adhering to strict veiling norm (full body burqa) in rural Bangladesh. The probability of female employment is lower in the conservative household. Conservative outlook is correlated with female self-employment and negatively related to non-farm salaried/casual work. There is a robust association between conservative outlook and the probability of females being overweight. Abstract: Following Identity Theory proposed by Akerlof and Kranton (2000), we conceptualize the interactions between conservative outlook and female wellbeing through influencing gender norms. Conservative households often prefer women to stay home, which correlates to female employment and decision-making autonomy, affecting female physical mobility and female nutrition. Finding a suitable indicator for conservative outlook is difficult as we typically lack household-level 'value survey'. In the fast modernizing context of rural Bangladesh, wearing burqa (veil) is often perceived as an indicator of socially conservative outlook. Using this insight, we process the data from the second wave of the Bangladesh Integrated Household Survey (BIHS) for 2015 to test the statistically robust association between household-level conservative outlook and gender-sensitive wellbeing indicators such as female employment, body mass index, and decision-making autonomy for the population of ever-married females aged 15–49 years old. After controlling for individual, household, and regional characteristics, and using sub-regional fixed effects, our findings suggest that living in conservative households is associated with lower probability of female employment. Females from conservative households are less likely to be in wage work or salaried jobs. The probability of being overweight is also higher for the females in conservative households as compared to non-conservative households.